Expert System Diagnosing Escherichia Coli (E-Coli) Bacteria in Refill Drinking Water with Certainty Factor Method - Juliansyah Juliansyah (Institute of Computer Science, 2021)
Maybe drinking water that is bought and consumed looks clean and clear like drinking water in general, but behind the clean and clear drinking water, the community cannot know what is contained in it. Cheap and affordable prices may be one reason people choose refill water from existing drinking water depots. No matter where the drinking water comes from, the most important thing is that daily drinking needs are met. Many depots that have sprung up at this time do not include a letter from the local health office stating that drinking water is suitable for consumption. Expensive costs and very difficult affairs make drinking water depot owners ignorant of the most important things that must be owned.